Research Regarding the Development of the Combustion Chamber of Internal Combustion Engines with Opposite Pistons - Horia Beles; Adrian Tusinean; Tudor Mitran; Florin Bogdan Scurt (Machines, 2023)
The reduction in environment pollutant emissions is one of the main challenges regarding ground transportation. Internal combustion engines, used especially in hybrid propulsion systems, may be a solution in the transition to fully electric cars. Therefore, more efficient engines in terms of fuel consumption, emission generation and power density must be developed. This paper presents research regarding the architecture of the combustion chamber of an internal combustion engine with opposed pistons. The aim of this research was to find a combustion chamber architecture that would enable the engine to perform close to the program target of: NOx < 3.5 g/kWh, smoke (FSN) < 1, specific fuel consumption (bsfc) < 198 g/kWh. Three variants of the combustion chamber’s architecture have been studied. After the experimental research, the conclusion was that none of them fully reached the target; however, significant improvements have been achieved compared with the starting point. As a result, further research needs to be carried out in order to reach and even exceed the target.